Production of PDMS microparticles by emulsification of two phases and their potential biological application. Issue 11 (24th July 2018) - Choi, Yo Han; Chung, Kwang Hyo; Hong, Hyo Bong; Lee, Woon Seob
ABSTRACT: Poly(dimethylsiloxane) (PDMS) has been widely used for prototyping of chips. Among many kinds of microstructures, it is almost impossible to make few micron-sized PDMS particles through microfluidic focusing methods because of the highly viscous property of uncured PDMS. Vigorous mixing of PDMS with water resulted in small, spherical particles was found. Furthermore, a simple and easy method was devised to assure an emulsion state. The PDMS–water emulsion was made using two syringes connected by a needle. This emulsion was rapidly heated to cure the PDMS within the emulsion. The resultant PDMS was examined using spectroscopic methods to determine the particulate morphology and size distribution. PDMS particles of which the size was around 1 µm with a narrow size distribution was produced. DNA delivery into cultured animal cells through these PDMS microparticles was also demonstrated as an illustrative application. These biologically inert microparticles will find many more practical applications with additional fine-tuning modifications based on discussed considerations. GRAPHICAL ABSTRACT: